Future Smart Foods for Cambodia: Harnessing the Potentials of Future Smart Foods for Zero Hunger in Cambodia - Silo, Sok (2018)
Sok Silo IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand